Gastrointestinal motility evaluation in children with orthostatic intolerance: Mayo Clinic experience. Issue 8 (1st June 2020) - Manini, Mhd Louai; Barazi, Adnan; Khemani, Disha; Abd‐Rabu, Rami; Absah, Imad; Fischer, Philip R.; Mara, Kristin; Stephens, Michael; Camilleri, Michael
Abstract: Objective: Orthostatic intolerance (OI) and autonomic dysfunction (AD) are common in adolescents and young adults. Patients experience multisystem symptoms including gastrointestinal (GI), postural orthostatic tachycardia syndrome (POTS), orthostatic hypotension (OH), or only symptoms of OI (SOI) without significant findings on 70‐degree head‐up tilt testing (HUT). We hypothesize that patients with POTS, OH, and SOI show differences in GI symptoms and motility test and that heart rate (HR) changes on HUT predict severity of GI dysmotility. Study design: From medical records of patients (<18 years) with OI, we collected demographics, presenting symptoms, GI manifestations, and GI motility testing. Data were compared between the 3 groups (POTS, OH, and SOI). We assessed changes in HR on HUT with changes on GI motility evaluation. Results: Two hundred twenty‐nine patients were included (73% females). Abdominal pain (65%), nausea (49%), vomiting (18%), and constipation (24%) were the most common GI symptoms. In patients who had motility evaluation, there were 27% (53/193) with delayed gastric emptying (GE) at 4 hours, 35% (32/92) with delayed colonic transit (CT), 55% (17/31) with reduced gastric accommodation (GA), and 75% (21/28) with dyssynergic defecation (DD). Among 100 POTS, 34 OH, and 95 SOI patients, no significant differences in GI symptoms or motility tests were identified and HR changes on HUT were not associated with changes on motility tests. Conclusion: GI symptoms are frequent in adolescents with OI and are associated with delayed GE, reduced GA, delayed CT, and presence of DD. Abstract : In a tertiary care center, about 35% of patients with orthostatic intolerance had delayed colonic transit at 24 hours. This was not different between patients with orthostatic hypotension, postural orthostatic tachycardia syndrome, or patients with only symptoms of orthostatic intolerance.